(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Breast cancer is the most common cause of malignancy-related deaths worldwide. Breast cancer related lymphedema is a common complication after surgical intervention, radiation therapy, or chemotherapy. Lymphedema is characterized by accumulation of abnormal protein rich fluid in interstitial spaces. Aims and objectives: The aim of this study is to compare the effectiveness of lympho-kinetic therapy and therapeutic compression wraps in managing arm swelling in breast cancer patients. Methods: The study was conducted in Allied Hospital I, Faisal Hospital and National hospital, Faisalabad. over a period of 3 to 4 months after obtaining approval from ethical committee of College of Rehabilitation Sciences. This study was a Randomized Clinical Trial and involved sample size of 42 female patients aged 18 or above suffering from arm lymphedema associated with breast cancer. They were allocated randomly into two equal groups by sealed pack opaque envelop technique. The intervention of Lympho-kinetic therapy was given to Group A and group B received Therapeutic Compression Wraps. In-addition both groups received standard treatment of Range of motion, Aerobic exercises, Diaphragmatic breathing, basic skin-care and self-management techniques for lymphedema. The measurements and readings were conducted pre- treatment and post-treatment with 4 weeks intervention time, five times per week, by using Kuhnke’s method for arm lymphedema and a Quick DASH outcome measure for quality of life compromise. Outcome measures: This study focused on reducing arm lymphedema, improve lymphatic drainage and to enhance quality of life disturbed by BCRL.